Pre-recorded Lectures - Is Anyone Watching? - Brown, S (SCHOLINK INC., 2022)
Pre-recorded lectures for students to watch at their own convenience appears attractive, but little evidence supports the notion that if recordings are available, they will be watched. A lack of engagement with pre-recordings may be exacerbated by the remote learning environments in response to population lockdowns and social isolation requirements. In this study, downloading of pre-recordings of lectures was examined in a large cohort introductory physiology course at a publicly funded university in New Zealand. Data from four semesters impacted by the COVID-19 pandemic were examined. A trend of decreasing engagement with recordings was evident in all semesters - from week 5 onwards, less than three-quarters of recorded material was downloaded, and from week 8 onwards, less than 60% of pre-recorded material was downloaded. This lack of engagement appeared to have little impact on course pass-rates, as these were consistently above 85% throughout the semesters in question. Data presented show that even when there was only the option for viewing a pre-recorded lecture, many students chose not to. Pre-recordings of lectures may seem to have value for some students, but they may be a poor substitute for attendance and physical engagement with the on-campus lecture experience.
Keywords: Lecture pre-recording; Student engagement; Remote learning; Physiology education